Pendampingan Digitalisasi Layanan Kesehatan Hewan melalui Website Satwa Sehat di Petshop Karimata, Jember - Afrianto, Eko; Ayuningsih, Ekatri (Cahaya Pengabdian, 2025)
Digitizing animal health services is a crucial step in improving access and quality of care for pet owners. This research aims to assist the Karimata Petshop in Jember in developing a "Satwa Sehat" website that provides animal health information and services. The method used was a participatory approach involving pet shop owners and animal health workers. The results of this assistance indicate an increased understanding of digitalization and the use of information technology in animal health services. This website is expected to raise public awareness of the importance of animal health and accelerate access to information.